IMPLEMENTASI NILAI-NILAI ANTIKORUPSI DALAM PEMBELAJARAN PENDIDIKAN PANCASILA - Prisko Yanuaris; Vinsensia Ledeng; ngadhi, Maria Kristina; Inda, Fransiska Kabrini; Moi, Maria Alfiana; Wale, Maria Yasinta (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
Corruption is a crime committed either individually or in groups, taking what is not their right with the aim of improving their own prosperity. According to the Big Indonesian Dictionary (KBBI), corruption is the act of accepting bribes, taking advantage of one's position to gain illegal profits. Factors that cause corruption can occur due to encouragement from within oneself, such as greed and dishonesty as well as a lack of gratitude and external stimulation factors such as encouragement from friends, family, and a materialistic lifestyle. This article was created to introduce anti-corruption values ​​to readers. The method applied is a descriptive qualitative approach, namely a method that only describes the condition of the variable object under study without making comparisons and is independent. The research method used is library research. The aim of this literature research is to actually shape the attitudes, mentality and character of students who in their daily and campus life reflect an attitude of life that is in accordance with anti-corruption values, so as to be able to create the nation's next generation that is free from the culture of corruption that is destroying the nation's economic life. and country